Compressive properties and creep resistance of a novel, porous, semidegradable poly(vinyl alcohol)/poly(lactic‐co‐glycolic acid) scaffold for articular cartilage repair. Issue 11 (31st December 2013) - Cao, Yi; Xiong, Dangsheng; Niu, Yuxiang; Mei, Yi; Yin, Zhaowei; Gui, Jianchao
ABSTRACT Tissue engineering for articular cartilage repair has shown success in ensuring the integration of neocartilage with surrounding natural tissue, but the rapid restoration of biomechanical functions remains a significant challenge. The poly(vinyl alcohol) (PVA) hydrogel is regarded as a potential articular cartilage replacement for its fair mechanical strength, whereas its lack of bioactivity limits its utility. To obtain a scaffold possessing expected bioactivity and initial mechanical properties, we herein report a novel salt‐leaching technique to fabricate a porous PVA hydrogel simultaneously embedded with poly(lactic‐co‐glycolic acid) (PLGA) microspheres. Through the investigation of environmental scanning electron microscopy, we found that the porous PVA/PLGA scaffold was successfully manufactured. The compression and creep properties were also comprehensively studied before and after cell culturing. The relationship between the compressive modulus and strain ratio of the porous PVA/PLGA scaffold showed significant nonlinear behavior. The elastic compressive modulus was influenced a little by the porogen content, whereas it went higher with a higher PLGA microsphere content. The cell‐cultured scaffolds presented higher compressive moduli than the initial ones. The creep resistance of the cell‐cultured scaffolds was much better than that of the initial ones. In all, this new scaffold is a promising material for articular cartilage repair. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40311.